GENETIC SOURCES OF RESISTANCE TO ROOT ROTS CYCORY FROM DIFFERENT ECOLOGICAL AND GEOGRAPHICAL ORIGIN - O. M. Vyutnova; T. U. Polyanina (Овощи России, 2018)
The main type of root chicory diseases are root rot of root crops. In unfavorable years, they affect up to 40-50% of root crops, which are culled from the test weight and are not paid for when the crop is delivered to the processing enterprises. The most common lesions of the roots of chicory various pathogenic species of fungi: Phoma rostrupii Sacc., Botrytis cinerea (P.) Fr. J, Erwiria carotovora (Jones) Holt. Production is in dire need of new varieties of root chicory, resistant to root rot both during the growing season and during long-term storage. To develop transgenic varieties among the many varieties to allocate genetic sources of this feature below in further breeding work to fix him in generations. The article presents the data on the study of the defeat of root crops of root chicory varieties of different ecological and geographical origin of different types of root rot in the collection nursery (including the provocative background) for 2015-2017 in the NonChernozem zone of the Russian Federation in the Rostov region of the Yaroslavl oblast. The best resistance to root rot were varieties Luxor (Holland) and Harpachi (Hungary), the roots of which did not have signs of root rot, varieties Petrovsky (Russia), Wixor (Holland) and Sleszka (Czech Republic) were weakly affected (less than 2%). During the long winter storage, the best on this basis, proven varieties Harpachi (Hungary), Spicak (Czech Republic) and Luxor (the Netherlands), which had been preserved. These varieties can serve as a source of resistance to root rot and can be involved in the selection process as a donor of this feature.